IMPLEMENTASI KURIKULUM BERBASIS AL-QURAN DAN SUNNAH DALAM PENDIDIKAN HOLISTIK DI GLOBE ISLAMIC SCHOOL - Soelaiman, Supini; Nina Marina; Jhonny Evendy; La Ilman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop an Islamic education curriculum based on the Qur’an and the Sunnah with the understanding of as-salaf, in accordance with the vision and mission of Globe Islamic School Batam: instilling tauhid, enlightening through the Qur’an, dignifying with noble character, and fostering multilingual competence (Arabic, English, and Bahasa Indonesia). The research employs a literature review with a qualitative descriptive and pragmatic approach. Primary data are derived from the Qur’an and the Sunnah (Prophet’s hadith), while secondary data come from books, journals, and online sources. Data collection techniques include documentation, interviews, and investigation. Data analysis follows the Miles and Huberman model, involving data collection, reduction, presentation, and verification. The findings emphasize the importance of aligning Islamic education curricula with societal needs while remaining faithful to the Qur’an and Sunnah with the understanding of as-salaf. Implementation in schools such as GIS Batam requires effective management, adequate resources, and collaboration among principals, teachers, and educational staff. Continuous evaluation is crucial to maintain the relevance and effectiveness of the curriculum. In conclusion, a Qur’an- and Sunnah-based curriculum with the understanding of as-salaf, tailored to GIS Batam’s vision and mission, must emphasize tauhid, noble character, and multilingual education, supported by effective management and collaboration to achieve holistic educational goals.